IMPLEMENTASI DEEP LEARNING BERBASIS PROBLEM-BASED READING UNTUK MENINGKATKAN LITERASI BACA KRITIS SISWA SEKOLAH DASAR - Uswatun Hasanah; Ulya Nurul Laili; Meidina Asmara Dewi; Milda ‘Ulya Rahmah; Hermanto (Jurnal Riset Pendidikan Dasar Dan Karakter, 2026)
This study aims to examine the effectiveness of implementing deep learning based on problem-based reading to improve the critical reading literacy of elementary school students within the Merdeka Curriculum framework. A quasi-experimental design with a pretest-posttest control group pattern was employed. The research subjects were 64 fifth-grade students of SDN 1 Kencong, divided into an experimental group (n=32) and a control group (n=32). A validated critical reading literacy test based on the PIRLS framework was used as the data collection instrument. Data were analyzed using an independent sample t-test. The results showed a significant difference between the critical reading literacy of the experimental group (posttest mean = 81.56) and the control group (posttest mean = 70.43), with t = 6.842 and sig. = 0.000 (p < 0.05). The gain score of the experimental group (19.22) was significantly higher than that of the control group (8.65). This study concludes that problem-based reading-based deep learning is effective in improving elementary students' critical reading literacy and is aligned with the Merdeka Curriculum's orientation toward the Pancasila Student Profile.